Pembuatan Prosedur Pengelolaan Arsip SK Pensiun di Badan Kepegawaian Daerah Provinsi Sumatera Barat - Oktari, Cahyani; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThis paper discusses the procedure for managing the retirement decision file archive at the Regional Personnel Agency in West Sumatra Province. The purpose of this study is to find out how the procedures for managing the retirement decision archive in the Regional Civil Service Agency of West Sumatra Province. This research method uses qualitative methods. Data is collected by interviews and collecting data directly from the original source with employees at the Regional Civil Service Agency of West Sumatra Province. Based on the discussion it can be concluded: 1) recording all data in the archive, all incoming data recorded to the ledger in accordance with the type, after recording the archive is divided into their respective processes; 2) data is transferred to the catalog, if the employee moves / retires, it will affect the number of catalogs used; 3) Removing files (from active to passive files), files whose files are still active, the data is first entered into the ledger and new stored in groups in a static storage area; 4) stored to a static storage area. The design process of making the book procedure for managing employee retirement SK records is as follows: 1) compiling the writing framework; 2) making book covers; 3) making introductory words; 4) making a table of contents; 5) making an introduction; 6) making the main contents of the book, the main elements contained in the book procedure for managing the employee retirement decree archive are a brief discussion of the profile of the West Sumatra Regional Personnel Agency, vision and organizational structure, then proceed to a discussion on the employee retirement decree archive procedure.Keywords: Management, Archives, Procedures